DEVELOPMENT OF HIGH LEGAL EDUCATION IN UKRAINE IN THE WORLD INTEGRATION PROCESS SYSTEM - Дроботова, Л. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2019)
In the article the author analyzes the state of higher education in general. The attention was paid to the development of higher legal education in particular, and the problems that have arisen and exist today are indicated. The ways of European integration education development and issues that require detailed study and systematization are considered. It is noted that any integration into the international space requires comprehensive modernization not only in the sphere of higher education, but also considerable efforts on the part of the legislative, normative base, and the creation of mechanisms that would conform to European standards, but also preserved spesial peculiarities of the national education. If we take into account the historical past of the development of education, then the state had an increased influence on all educational functions of higher educational institutions, in particular, the universities founded in the XIX century. The state structures regulated the range of issues related to the definition of the list of academic disciplines, which was at universities for law students, a list of departments of law schools, the establishment of rules for admission, as well as the transfer and graduation of specialists was proposed. By the way, with the creation of the Ministry of Education, a special set of requirements added to the content of teaching at the law schools. It is noted that the state also contributed to the development of legal science, defining the teaching of a specific course of study disciplines in law schools. The legal acts, the so-called circulars, regulating the relations connected with the educational activity of higher educational establishments created. Universities were only able to fill gaps in legal regulation with local regulations. The author mentions some of the shortcomings of the new laws created by the state, in which there is a discrepancy between the expansion of academic, financial and organizational autonomy of higher educational institutions, no norms that would ensure democracy within higher education institutions